Socialist People's Libyan Arab Jamahiriya : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2005)
This 2004 Article IV Consultation highlights that the Libyan economy remains largely state controlled and heavily dependent on the oil sector. Since the lifting of the Libya-specific trade sanctions of the United Nation and United States in September 2003 and September 2004, respectively, the pace of economic and structural reforms has picked up somewhat, with the implementation of measures aimed at enhancing the role of the private sector in the economy. However, these reforms continue to be implemented in an ad hoc and nontransparent manner.